Species Identification of Campylobacter jejuni and Campylobacter coli Isolates from Raw Poultry Products by MALDI–TOF MS and rRNA Sequence Analysis. (29th January 2020) - Sulaiman, Irshad M; Hsieh, Ying-Hsin; Simpson, Steven
Abstract: Background: Campylobacter is a genus of Gram-negative bacteria. It is considered one of the leading cause of diarrheal illness worldwide. Incidence of human campylobacteriosis has increased significantly during recent decades; the increase has been directly linked with the advancement made in Campylobacter detection methods. C. jejuni and C. coli are the two major human-pathogenic species that can colonize poultry and cause foodborne illness and outbreak. Objective: This study was carried out to rapidly identify Campylobacter -like isolates recovered from raw poultry products by matrix-assisted laser desorption ionization (MALDI)–time-of-flight (TOF) MS and DNA sequencing of 16S and 23S ribosomal RNA (rRNA) regions. Methods: Twenty-seven isolates of Campylobacter -like organisms were isolated from raw poultry products and cultured on blood agars for MALDI–TOF MS analysis and DNA isolation. For each isolate, one to two colonies were directly spotted on the VITEK MS analysis. Genomic DNA was extracted from overnight bacterial culture. Afterward, two-directional Sanger sequencing of rRNA gene was performed to confirm species identification on an ABI 3500xL Genetic Analyzer. Results: The VITEK MS could provide species-level identification for all 27 Campylobacter -like bacterial isolates (including 13 isolates as C. jejuni and 14 isolates as C. coli ). Species identification attained by the VITEK MS matched completely with the rRNA sequence characterization data. Conclusions: Based on the restricted number of target strains and agar plates, MALDI–TOF MS and rRNA sequence analysis can be used for rapid identification of C. jejuni and C. coli isolates. Highlights: MALDI–TOF MS and rRNA sequencing can provide species identification of C. jejuni and C. coli isolates.